The HEAT-Registry (HEmatopoietic Affection by Testosterone): comparison of a transdermal gel vs long-acting intramuscular testosterone undecanoate in hypogonadal men. (31st December 2022) - Zitzmann, Michael; Cremers, Jann F.; Krallmann, Claudia; Kliesch, Sabine
Abstract: Context: Testosterone (T) therapy of hypogonadal men requires stable kinetics, tolerance and attenuation of symptoms. Both intramuscular injections of the long-acting ester T undecanoate (TU) and transdermal application of T gel offer a proven efficacy. As T has marked effects on hematopoiesis, an elevation of hematocrit has to be considered during T therapy. Objective: To compare the effects of a transdermal T gel with long-acting intramuscular TU on hematopoiesis, controlling for age, diagnosis, androgen receptor susceptibility and obesity. Design: Prospective two-arm open registry, minimum duration of 26 weeks per patient. Putative modulators of erythropoiesis entering regression models were type of medication, type of hypogonadism, delta of total testosterone concentrations, waist circumference, age as well as (in a sub-group) androgen receptor gene CAG repeat length. Setting: Tertiary university based andrological outpatient department. Patients: 802 hypogonadal men, 498 receiving T gel and 304 receiving intramuscular TU, median age 40 years (interquartile range = 25). Results: Follow-up visits after initiation of treatment occurred between treatment weeks 26-30. Serum T concentrations increased markedly in both patient groups. Men receiving intramuscular TU exhibited an increased hematocrit (>50%) to a significantly higher amount than men receiving T gel (69/304 vs. 25/498, p  < 0.001). Corresponding results were seen for higher values of hematocrit (>52% and >54%). Advanced age ( p  = 0.009), higher waist circumference ( p  = 0.01), higher delta testosterone ( p  = 0.007) and functional vs classical hypogonadism ( p  = 0.04) contributed to the effect in stepwise multiple regression models. Attenuated androgen action (longer androgen receptor CAG repeats) mitigated the effect ( p  = 0.01) in a subgroup of 574 patients. Men with anemia (hemoglobin ≤12.7 g/dl) were more likely to move out of the pathological range when receiving TU vs T gel (41/53 vs. 49/89 p  = 0.01). Conclusions: T substitution with intramuscular TU or T gel increase T concentrations effectively. Long-acting TU leads to a higher rate of hematocrit levels >50%, whilst at the same time it seems to be more efficient to ameliorate anemia in the subgroup of respectively affected hypogonadal patients . This applies especially to obese older men with functional hypogonadism.